Call for Waterfront to be more disabled friendly - Abdul Rahim, Asiah (2011)
KUCHING: Many tourists may give the Kuching Waterfront a favourable rating but a study has called for more features to be enhanced for people with special needs. The study, conducted in 2008, pointed out that bollards and curb cuts built along the Waterfront made it difficult for the disadvantaged especially those in wheelchairs to move around. It was also raised that no accessible parking had been provided for people with special needs. In addition, the public toilets at Kuching Waterfront were built in such a way that they are unfriendly to the disadvantaged.